Towards Better Governance on Biosafety and Biosecurity: China’s Advances and Perspectives in Medical Biotechnology Legislation - Xue, Yang; Shang, Lijun (Frontiers in Bioengineering and Biotechnology, 2022)
The current and potential biosafety and biosecurity risks of biotechnology will go beyond national borders, as will possible societal effects. Despite the Chinese government's best attempts in recent years to limit the risks associated with biotechnology, loopholes are inevitable when developing governance policies. Policymakers in China have now incorporated biotechnology-related biosafety and biosecurity into the national strategic goals of a "people-centered" approach to establish and foster an ecological civilization, particularly in the aftermath of the "He Jiankui's affair." Instead of relying on a large number of administrative regulations with no actual punitive effect, China is attempting to integrate a patchwork of existing regulations and measures relating to the emerging field of biotechnology into a comprehensive legal framework and has begun to address the lack of a legal basis for assumed responsibilities for technological damages and dispute resolution procedures. This paper firstly provides a systematic analysis of China's biotechnology legal regime, which follows the "precautionary principle," and then further analyzes some of the legislative challenges in governing biotechnology risks, in the context of China upgrading its regulatory and legal regime in biotechnology in the last three years in line with the current pace of technological progress: (1) a predicament to maintain a delicate balance between the regulations' specificity and excessive generality; (2) a dilemma between the demand for cooperation and the distribution of authority and responsibility among multiple government departments and agencies; (3) a short of nontraditional scientists’ provisions; (4) a lack of effective regulatory restraint on emerging biotechnologies; and (5) consequences of the relative regulations resulting insufficient efforts in biologists’ biosecurity awareness, and moral self-discipline, particularly in terms of execution. The "top-down" formulation of general objectives by the active political leadership and "bottom-up" innovation in the implementation are the keys to achieving these goals. Given the rapid advancements in biotechnology, countries around the world must examine the governance landscape around biosafety and biosecurity and quickly consider options for a comprehensive, credible, and long-lasting regulatory framework for their own, and the lessons and experiences learned from China's governance experience will help chart a scalable future roadmap.